2022
DOI: 10.1158/2643-3230.bcd-21-0222
|View full text |Cite
|
Sign up to set email alerts
|

CD20-Targeted Therapy Ablates De Novo Antibody Response to Vaccination but Spares Preestablished Immunity

Abstract: To obtain a deeper understanding of poor responses to COVID-19 vaccination in patients with lymphoma, we assessed blocking antibodies, total anti-spike IgG, and spike-specific memory B cells in the peripheral blood of 126 patients with lymphoma and 20 age-matched healthy controls 1 and 4 months after COVID-19 vaccination. Fifty-five percent of patients developed blocking antibodies postvaccination, compared with 100% of controls. When evaluating patients last treated from days to nearly 18 years prior to vacci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 25 publications
3
44
1
Order By: Relevance
“…We observed lower IgG-binding titers against the Wuhan strain spike protein in patients with NHL/CLL compared with healthy controls, especially after recent anti-CD20-directed therapy. While this observation has been reported, [16][17][18][19]21,[26][27][28] we further improve on our understanding of antibody responses in patients with NHL/CLL by also showing decreased IgM and IgA titers, which may confer protection at mucosal surfaces. 37 Additionally, our lymphocyte profile analysis provides biologic context for the decreased response observed after recent anti-CD20-directed therapy.…”
Section: Discussionsupporting
confidence: 53%
“…We observed lower IgG-binding titers against the Wuhan strain spike protein in patients with NHL/CLL compared with healthy controls, especially after recent anti-CD20-directed therapy. While this observation has been reported, [16][17][18][19]21,[26][27][28] we further improve on our understanding of antibody responses in patients with NHL/CLL by also showing decreased IgM and IgA titers, which may confer protection at mucosal surfaces. 37 Additionally, our lymphocyte profile analysis provides biologic context for the decreased response observed after recent anti-CD20-directed therapy.…”
Section: Discussionsupporting
confidence: 53%
“…However, our data suggest that vaccination prior to B cell-targeted therapy may be important to achieve long-term benefits. In support of this notion, two recent studies, with a relatively small number of patients, provide evidence that SARS-CoV2 vaccination prior to anti-CD20 mAb had superior induction of antibody responses compared to when the agents were administered in reverse order (46, 47). In summary, our findings highlight the discordance between de novo and pre-existing antibodies.…”
Section: Discussionmentioning
confidence: 89%
“…Levy et al. [19] evaluated the response to COVID-19 vaccine in 126 lymphoma patients who received rituximab by measuring antibodies to viral spike proteins. The last dose of rituximab varied from days to 18 years prior the vaccine.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Results showed that patients who received rituximab within 12 months prior to vaccine administration are less likely to develop antibodies. 10 of the 15 patients who received the vaccine prior to initiation of rituximab developed antibodies [19] . The optimal timing of receiving COVID-19 vaccination to mount a response after finishing rituximab therapy is unknown yet.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%